Motor competence in first- and second-grade schoolchildren in the Araucanía region, Chile - Martinez-Lopez, Nicolas (2021)
Motor competence is a significant component for participation in the culture of play, sports, and physical activity. Its development is therefore key at the early stages of a child’s journey through the educational system. The purposes of this study were to describe performance in the motor competence of Object Control and Body Control in first- and second-grade elementary school students in Chile, to determine the relationship between this motor competence and age, and to establish the existence of potential sex-related differences among the students. A quantitative approach was used, as this was a non-experimental, cross-sectional, descriptive-correlational study. Participants included 289 schoolchildren (51.2% girls, 48.8% boys) between six and eight years of age in five schools of the region of La Araucanía, Chile. The MOBAK 1-2 test was used for assessing the motor competence in two dimensions (Object Control and Body Control). In order to establish the relationship between motor competence and age, Spearman’s rho coefficiient was used; and Mann-Whitney’s U test was used to determine the existence of sex-related differences, determining the extent of the effect through superiority probability (SP) calculation. The results indicate that age is positively related to Object Control (p < .001, r = .315) and Body Control (p < .001, r = .261). When comparing motor performances according to sex, boys showed better results than girls in motor tasks associated to Object Control (U = 13533.000, Z = 4.439, p < .001, PSest = .61), whereas no statistically significant differences were found in Body Control. Both age and sex in students are variables associated to the development of this motor competence. These results provide relevant information for designing pedagogical strategies that seek to foster motor competence in an optimal, equitable manner.